Relative Abundance Trends of Bird Populations in High Intensity Croplands in the Central United States. (7th August 2018) - Belden, Jason B; McMurry, Scott T; Maul, Jonathan D; Brain, Richard A; Ghebremichael, Lula T
ABSTRACT: Declining bird populations across the United States have been noted in a number of studies. Although multiple explanations have been proposed as causes of these declines, agricultural intensification has often been suggested as a significant driver of bird population dynamics. Using spatially explicit USDA‐NASS Cropland Data Layer, we examined this relationship by comparing bird count data from the Breeding Bird Survey collected between 1995 and 2016 across 13 states in the central United States to corresponding categorical changes in land cover within a 2‐km radius of each survey transect. This approach allowed us to compare the slopes of counts for 31 species of birds between grassland‐ and cropland‐dominated landscapes and against increasing levels of cropland (all types combined) and pooled corn and soybean land cover types. Nearly all birds demonstrated significant responses to land cover changes. In all cases, the number of species exhibiting positive or negative responses was comparable, and median differences in percent change per year ranged from −0.5 to 0.7%. Species that responded either positively or negatively did not appear to fall into any particular foraging guild. If changes in agricultural practices are a major cause of declines, we would expect to see it across the spatial scale studied and across the majority of species. While these results do not rule out potential agricultural effects, such as toxicity resulting from pesticide exposure, which may have species‐specific or localized effects, a variety of factors related to habitat are likely the most significant contributor overall. Given these results over a large spatial scale basis (multistate) and across numerous bird species, there is not a broad general trend of greater decline in crop‐intensive areas. Integr Environ Assess Manag 2018;14:692–702. © 2018 SETAC Key Points: When comparing relative trends in abundance, the majority of bird species showed significant differences based on the extent of cropping. The number of species exhibiting positive responses to increased crop intensity tended to equal or exceed those species showing a significant negative response. Species that responded either positively or negatively did not appear to fall into any particular foraging guild. If a shift in current agricultural practices is a major cause of declines, we would predict to see decreased relative abundance trends in more heavily cropped areas across the spatial scale studied and across the majority of species, which was not observed.